Pelatihan Pembuatan Website Menggunakan Elementor pada Produk Bumdes Banjarworo, Kabupaten Tuban sebagai Sarana Promosi - Nasa Zata Dina; Aji Akbar Firdaus; Riky Tri Yunardi (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The welfare of the community on all fronts is one of Indonesia's national ideals. The village, as the smallest community in the state society, is often the forgotten part of the effort to achieve this. Therefore, legislation that regulates village problems is made in the hope that the welfare of the village community can be achieved. One of the things regulated in the law on villages is the BUMDes. BUMDes itself is an agency that plays an important role in improving the village economy. In this article, we will discuss the role of BUMDes as an economic driver using the Banjarworo Village case study. The research method used in this article is a qualitative research method with data collection techniques in the form of interviews, field observations, and literature studies through books, journals, and related websites. After the data was collected, data triangulation from the three data collection techniques was carried out to obtain the validity of the data used in this paper. The results obtained are that BUMDes can play an effective role in improving the economy in Banjarworo Village because they can develop MSMEs in the village by increasing branding and expanding the marketing reach of the products produced.